Learning through period and physical time - Teresa Backhaus; Steffen Huck; Johannes Josef Leutgeb; Ryan Oprea (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
We demonstrate in a laboratory experiment in which subjects play a two-player Cournot-Tullock game over hundreds of periods of varying length that full accounts of subjects' learning requires the consideration of, both, 'period time' and 'physical time.'
Keywords: C73; C92; 330; Cournot oligopoly; Laboratory experiment; Learning; Time